Preparation of n-type semiconducting polymer nanoarrays by covalent synthesis followed by crystallization1. (2nd March 2015) - Fouzia, Begum; Ferguson, John; McKenna, Kelly; McNamara, Louis E.; Hammer, Nathan I.; Rathnayake, Hemali
<x xml:space="preserve">Abstract</x> N-type semiconducting polymer nanoarrays derived from poly(perylenediimide-bridged silsesquioxanes) were prepared by in situ covalent synthesis followed by solution crystallization. Their crystallinity and polymer chain ordering support their photophysical behavior in solid state.